Multiple Lithiasis of Single Kidney. Lithotomy. Continous Refrigerating Renal Perfusion Using Perfusion Pump. - Corio, Ernesto; Clark, Omar; Lockhart, Jorge; Estefan, Alberto; Gateño, Nisso (Cirugía del Uruguay, 1980)
A patient suffering fro'm multiple lithiasis in single kidney and who had been previously unsuccessfully treated by surgery", was operated while in hypothermia induced by continous refrigerating puisatile perfusion by perfusion pump.